PENGARUH ELECTRONIC WORD OF MOUTH TERHADAP PURCHASE INTENTION PRODUK KARYA NARAPIDANA - Suhada, Aqshal Surya; Kusmiyanti, Kusmiyanti (Journal of Management Small and Medium Enterprises (SMEs), 2024)
This study aims to see whether electronic word of mouth has a direct impact on public buying interest in products made by prisoners at the Lembaga Pemasyarakatan Tasikmalaya Class IIB. This research method uses quantitative methods with a population and sample of 108 Instagram social media followers where the entire population is sampled. There are a total of 9 statement items to be questioned and distributed to all officers. The results of the determination test analysis show that the electronic word-of-mouth variable has an influence of 21% on the interest in buying products made by prisoners. This research hypothesis concludes that there is an influence of electronic word of mouth on the interest in buying products made by prisoners of Lembaga PemasyarakatanTasikmalaya Class IIB. Keywords: Marketing; Purchase Interest; Products; Prisoners